Microglia activation and cone disruption are the main alterations in the retina of human donors with COVID‐19 - Albertos‐Arranz, Henar; Sánchez‐Sáez, Xavier; Martínez‐Gil, Natalia; Noailles Gil, Agustina; Calvo Andrés, Ramón; Monferrer Adsuara, Clara; Remoli Sargues, Lidia; Montero Hernández, Javier; Cuenca, Nicolás (Acta ophthalmologica (Oxford, England), 2022)
Purpose The presence of SARS‐CoV‐2 in the eye and different alterations in the ocular tissues have been described. However, the health state of the retinal cells in these patients is unknown. The aim was to analyze the morphology of the retinal cells and glial activation in human donor deceased by COVID‐19. Methods Retinas from human donors with COVID‐19 (n = 9) and from a group control (n = 5) were analyzed. Samples were obtained from the General University Hospital Consortium of Valencia. Photoreceptors, Müller cells, astrocytes, microglia and retinal blood vessels and the location of ACE2 protein were studied through immunohistochemistry staining in cross‐sections and wholemount retinas (using calbindin, recoverin, GFAP, CRALBP and Collagen Type IV, Iba‐1 and ACE2). Confocal microscopy and a quantitative analysis of Iba‐1 positive cells were performed. Results The mean age of COVID‐19 and control group was 77 ± 11 and 68 ± 7 years, respectively. Müller cells, retinal pigment epithelium and outer segment of photoreceptors showed ACE2 immunostaining. The staining of ACE2 protein in the outer segment of photoreceptors was weaker in some COVID‐19 patients. Several patients presented a swelling of the axon terminal of cone photoreceptors and disruptions in the structure of Müller cells. The ramified resident microglial cells changed to an ameboid shape and most of these cells migrated to the retinal vessels. Moreover, the microglia activation in the retina of COVID‐19 patients was confirmed by a reduction of the total area occupied by these cells. Conclusions Morphological alterations in the cone photoreceptors and Müller cells, variations in the staining of ACE2 protein and microglia activation was found in human donor retinas with COVID‐19. Support: FEDER‐PID2019‐106230RB‐I00. FPU16/04114, FPU18/02964. RETICS‐FEDER RD16/0008/0016. Retina Asturias/Cantabria. FARPE‐FUNDALUCE. IDIFEDER/2017/064.